"What" and "where" perception in left- and right-handers: an erp study - Kachynska, Tetiana V.; Kotsan, Ihor Ya.; Kuznetsov, Illya P.; Dmytrotsa, Olena R.; Качинська, Тетяна Валеріївна; Коцан, Ігор Ярославович; Кузнецов, Ілля Павлович; Дмитроца, Олена Романівна (Wiley, 2012)
Human motor functions lateralization may probably be accompanied by specific realization of sensor and cognitive functio especially in tasks, related to processing of visual object location and orientation. We studied the ERP characteristics under conditions of adequate functional load. Two groups took part in the study, 14 persons each: dextrals and sinistrals. ERPs w recorded during two experimental situations. ICA-analysis of obtained ERPs showed specificity regarding the number and localization of evoked activity sources. Thus, the manual asymmetry is crucial for the functioning of the object classification system, while the functioning of object location estimation system is less sensitive to the type of hand preference.
Keywords: Dextral; Sinistral; Evoked activity; ICA-analysis